Effects of added zinc and copper on growth performance and carcass characteristics of finishing pigs fed ractopamine HCl - Coble, Kyle F.; Paulk, Chad B.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 253 finishing pigs (PIC 327 × 1050; initial BW 204 lb) were used in a 28-d study to determine the effects of added Zn (Availa-Zn; Zinpro Corp., Eden Prairie, MN), Cu (Availa-Cu; Zinpro Corp.), or both to diets containing ractopamine HCl (RAC; Paylean; Elanco Animal Health, Greenfield, IN) on growth performance and carcass characteristics. Pens of pigs were randomly assigned to 1 of 5 treatments and balanced on average pig weight with 7 to 8 pigs per pen. Treatments included a control diet without RAC (negative control) and 4 diets containing 9 g/ton RAC with or without added Zn (50 ppm) or Cu (125 ppm) in a 2 × 2 factorial. Overall, pigs fed RAC had increased (P < 0.01) ADG and improved F/G, which resulted in approximately a 15.5-lb heavier (P < 0.01) pig compared with those fed the negative control diet. Pigs fed added Zn had decreased (P < 0.05) ADG and tended to have decreased (P < 0.09) ADFI. Pigs fed added Cu also tended (P < 0.10) to have decreased ADG. No differences were observed in F/G when Zn or Cu was added to the diet. Hot carcass weight, carcass yield, loin depth, and percentage lean increased (P < 0.01) in pigs fed the positive control diet containing RAC compared with those fed the negative control diet, whereas backfat was unaffected. Carcass characteristics were not affected by added Zn or Cu. Feed cost and revenue increased (P < 0.01) for pigs fed the positive control diet containing RAC by approximately $9.63 and $10.08, respectively, compared with pigs fed the negative control diet; however, no difference was observed in feed cost per lb of gain. Income over feed cost (IOFC) did not differ in pigs fed the negative or positive control diet. Adding Zn decreased (P < 0.05) revenue per pig, and adding Cu tended to increase (P < 0.06) feed cost per lb of gain and reduce (P < 0.10) revenue per pig. There were no differences in IOFC between diets containing added Zn and no added Zn. Added Cu reduced (P < 0.05) IOFC. In summary, growth and carcass characteristics improved in pigs fed dietary RAC as expected, but adding Zn, Cu, or both to diets containing RAC did not improve growth performance, carcass characteristics, or IOFC. Adding copper actually reduced IOFC due to the added expense.
Keywords: Finishing pig; Zinc; Copper; Ractopamine HCl